Living in the dry zone: Stable isotope insights into palaeodiet in ancient Myanmar. (April 2023) - Willis, Anna; Roberts, Patrick; Kyaw, Myo Min; Win, Thu Thu; Pradier, Baptiste; King, Charlotte; Ilgner, Jana; Lucas, Mary; Cook, Amanda; Piper, Philip; Pryce, T.O.
Highlights: Oakaie and Nyaung'gan are prehistoric sites in Myanmar (ca. 1300-700BC). 1300-700BC is the transitional late Neolithic to the early Bronze Age period. Individuals have higher δ 13 C values than those from Mainland Southeast Asian sites. Individuals have comparable δ 13 C values to those from Chinese sites. δ 13 C and δ 18 O provide an insight into ancient subsistence in Myanmar. Abstract: Southeast Asia is becoming a region of increasing interest in discussions of past migration, the origins of agriculture, and past impacts of human land-use change on environments. Myanmar, situated at a geographic and cultural crossroads between East, South and Mainland Southeast Asia, is potentially a critical region for exploring these themes. However, direct data relating to subsistence in the region has been lacking. Here, we apply stable carbon and oxygen isotope analysis to tooth enamel from humans and associated fauna to examine the subsistence economy of two communities from Myanmar, Oakaie and Nyaung'gan, spanning the transitional period from the late Neolithic to the early Bronze Age (ca. 1300-700BC). Situated within the broader regional and local environmental context, our data demonstrate the δ 13 C values of the individuals from the communities of Oakaie and Nyaung'gan are significantly higher, and the δ 18 O values are significantly lower, than individuals from the other sites in Southeast Asia, however, neither are significantly different to the Chinese sites and they overlap broadly with individuals from Mayutian in Southern Yunnan Province. These findings provide a unique insight into the subsistence economy of the ancient inhabitants of the Central Dry Zone of Myanmar.